Staphylococcus Aureus Infecton in Various Skin Diseases: (1) Modulation of Antibody Level to Staphylokinase - KABURAGI, Yutaka; KITAMURA, Keijiro; GOTO, Yoshiko; IZAKI, Seiichi (Skin research, 1996)
An adequate serum marker for Staphylococcus aureus-infection has not been commonly utilized yet in clinical dermatology, when compared to ASO and ASK for streptococcusinfection. We measured antibody level of staphylokinase (SAK), a protein product of Staphylococcus aureus, in various skin diseases, in order to assess practical and investigative significance of and SAK. Levels of and SAK-IgG, IgA and IgM were measured with ELISA technique. In comparison to normal healthy subjects, patients with cellulitis and other infectious skin disease showed significantly high antibody level, and this level was not correlated to ASO or ASK. Patients with atopic dermatitis, nummular eczema, urticaria, erythema exsudativum mutiforme and erythema nodosum showed elevated anti SAK, suggesting a role of staphylococcal infection in those diseases. Western blotting confirmed specific immunoreaction bands to SAK in the blood samples from the patients with high anti-SAK titer. We conclude that antibody to SAK may be a worthy indicator to investigate the effects of Staphylococcus aureus-infection in various skin diseases.